The Effect of Using Strategy Word Square Toward Students’ Vocabulary Mastery in Descriptive Text at MTS Darussalam Parmeraan Academic Year 2021-2022 - Sihombing, Sella Syah Putri; Muhammad Khalid (Education & Learning, 2023)
Vocabulary is one of the elements in language. In English there four skills, they are listening, speaking, reading, and writing. In mastering English, the basic thing that students have to learn and understand is vocabulary, because the mastery of vocabulary influence to another skills in English. The objective of this research was to know whether using word square game is able or not to improve students’ vocabulary mastery at the second year of MTs S Darussalam Parmeraan. This research was aimed to find out the improvement of students’ vocabulary mastery after giving treatment using word square game. This research used pre-experimental design, with one group pre-test and post- test. The pre-test was given before treatment to know their prior vocabulary, while the post-test was given after treatment to know their vocabulary after getting treatment. The population of this research was the second year of MTs S Darussalam Parmeraan. The researcher took VII.3 as the sample which was consisting of 24 students. The result of this research was found that there was a significant between the pre-test and post-test. The mean score of pre-test was 53.8, while the mean score of posttest was 72.33. The result finding that score of t-test value was 8.73 higher than the score of t-table was 1.714 for the level significance 0.05 degree of freedom 23. Based on the result above, the researcher concluded that using word square game was able to improve students’ vocabulary mastery at the second year of MTs S Darussalam Pameraan.